Antibody Response in Immunocompromised Patients After the Administration of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Vaccine BNT162b2 or mRNA-1273: A Randomized Controlled Trial. (2nd March 2022) - Speich, Benjamin; Chammartin, Frédérique; Abela, Irene A; Amico, Patrizia; Stoeckle, Marcel P; Eichenberger, Anna L; Hasse, Barbara; Braun, Dominique L; Schuurmans, Macé M; Müller, Thomas F; Tamm, Michael; Audigé, Annette; et al.
Abstract: Background: BNT162b2 by Pfizer-BioNTech and mRNA-1273 by Moderna are the most commonly used vaccines to prevent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. Head-to-head comparison of the efficacy of these vaccines in immunocompromised patients is lacking. Methods: Parallel, 2-arm (allocation 1:1), open-label, noninferiority randomized clinical trial nested into the Swiss HIV Cohort Study and the Swiss Transplant Cohort Study. People living with human immunodeficiency virus (PLWH) or solid organ transplant recipients (SOTR; ie, lung and kidney) from these cohorts were randomized to mRNA-1273 or BNT162b2. The primary endpoint was antibody response to SARS-CoV-2 spike (S1) protein receptor binding domain (Elecsys Anti-SARS-CoV-2 immunoassay, Roche; cutoff ≥0.8 units/mL) 12 weeks after first vaccination (ie, 8 weeks after second vaccination). In addition, antibody response was measured with the Antibody Coronavirus Assay 2 (ABCORA 2). Results: A total of 430 patients were randomized and 412 were included in the intention-to-treat analysis (341 PLWH and 71 SOTR). The percentage of patients showing an immune response was 92.1% (95% confidence interval [CI]: 88.4–95.8; 186/202) for mRNA-1273 and 94.3% (95% CI: 91.2–97.4; 198/210) for BNT162b2 (difference: -2.2%; 95% CI: -7.1 to 2.7), fulfilling noninferiority of mRNA-1273. With the ABCORA 2 test, 89.1% had an immune response to mRNA-1273 (95% CI: 84.8–93.4; 180/202) and 89.5% to BNT162b2 (95% CI: 85.4–93.7; 188/210). Based on the Elecsys test, all PLWH had an antibody response (100.0%; 341/341), whereas for SOTR, only 60.6% (95% CI: 49.2–71.9; 43/71) had titers above the cutoff level. Conclusions: In immunocompromised patients, the antibody response of mRNA-1273 was noninferior to BNT162b2. PLWH had in general an antibody response, whereas a high proportion of SOTR had no antibody response. Abstract : This randomized trial confirmed the noninferiority of the severe acute respiratory syndrome coronavirus 2 vaccine mRNA-1273 compared with BNT162b2 in terms of antibody response in immunocompromised patients. Although people with human immunodeficiency virus had a sufficient antibody response, a high proportion of transplant recipients had no antibody response.